ORAL DELIVERY OF SILVER NANOPARTICLES – A REVIEW - JOSHI, VEDAMURTHY; SULTHANA, FIRDOS; RAMADAS, DINESHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Silver nanoparticles (NP) offer many applications in the science and technology. Oral delivery of such tiny particles results in enhanced drug absorption, reduction in dose, and minimize adverse effects. This review focuses on the mainly on the effects in the gastrointestinal tract along with its in vitro and in vivo studies carried on the silver NP. In this review, we compiled some of the extensive research in the field of silver NP, highlighting some of the most recent trends in the area. Search was carried in English language using Science direct, PubMed, and Google scholar search engines. The effects of silver NP on gastrointestinal tract such as absorption, distribution, metabolism, and elimination were compiled in this review. In addition, selected in vitro and in vivo studies related to the same are discussed. The accumulation of silver NP leading to Arginia condition also emphasized in the study. Silver NP and herbal silver NP in oral delivery can be exploited for the further safer and effective treatment.